Observation of the decay [lambda]0b→[lambda]c+pp̄ π− - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Comerma-Montells, Albert; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Kecke, Matthieu; Kolpin, Michael; et al. (Physics letters, 2018)
The decay Λb0→Λc+pp‾π− is observed using pp collision data collected with the LHCb detector at centre-of-mass energies of s=7 and 8 Tev, corresponding to an integrated luminosity of 3 fb−1. The ratio of branching fractions between Λb0→Λc+pp‾π− and Λb0→Λc+π− decays is measured to beB(Λb0→Λc+pp‾π−)B(Λb0→Λc+π−)=0.0540±0.0023±0.0032. Two resonant structures are observed in the Λc+π− mass spectrum of the Λb0→Λc+pp‾π− decays, corresponding to the Σc(2455)0 and Σc⁎(2520)0 states. The ratios of branching fractions with respect to the decay Λb0→Λc+pp‾π− areB(Λb0→Σc0pp‾)×B(Σc0→Λc+π−)B(Λb0→Λc+pp‾π−)=0.089±0.015±0.006,B(Λb0→Σc⁎0pp‾)×B(Σc⁎0→Λc+π−)B(Λb0→Λc+pp‾π−)=0.119±0.020±0.014. In all of the above results, the first uncertainty is statistical and the second is systematic. The phase space is also examined for the presence of dibaryon resonances. No evidence for such resonances is found.
LHCb Collaboration: R. Aaij, P. d'Argent, S. Bachmann, D. Berninghoff, A. Comerma-Montells, M. Dziewiecki, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, M. Kecke, B. Khanji, M. Kolpin, R. Kopecna, B. Leverington, J. Marks, D.S. Mitzel, S. Neubert, M. Neuner, A. Piucci, N. Skidmore, M. Stahl, S. Stemmle, U. Uwer, A. Zhelezov [und weitere]
Im Titel wird Lambda als griechischer Buchstabe dargestellt
Im Titel ist das Minus-Zeichen hochgestellt
Im Titel sind "0" und "b" untereinander geschrieben: "0" hochgestellt, "b" tiefgestellt
Im Titel sind "+" und "c" untereinander geschrieben: "+" hochgestellt, "c" tiefgestellt